Understanding Greed in Literature: A Dialogue of Textual and Social Interpretations of Money - Saifur Rohman (Balai Bahasa Provinsi Bali, 2025)
This paper focuses on the ethical issues facing Indonesian people in literature and reality. The material object is novel 86 (